Effects of Replacement of Soybean Meal with Rapeseed Meal on Organs Weight, Some Blood Biochemical Parameters and Performance of Broiler Chicks - Taraz, Z.; Jalali, S.M.A.; Rafeie, F. (International Journal of Poultry Science, 2006)
Experiment was designed to investigate the possibility of using rapeseed meal in the diet of broiler chicks. The rapeseed meal was replaced to soybean meal with the levels of 0 (control), 25, 50, 75 and 100 percent for the periods of starter (1-21 d), grower (21-42 d) and finisher (42-49 d) feeding systems. The rate of body weight gain was lower in the 100% treatment during the starter, grower and total feeding periods, while there was no difference between the control and 25% treatments. The feed conversion ratio of 100% replacement for the starter and grower feeding periods were statistically different (P< 0.05) from the control and 25% treatment and between control and 25% treatment no difference was found. At the age of 49 days, the lowest concentration of gamma glutamyltransferase, triiodothyronine hormone and ratio of triiodothyronine to thyroxin in blood serum of chicks were seen in 100% treatment (P< 0.05). The size of liver and relative weight of gallbladder increased (P< 0.05) with increasing dietary rapeseed meal. The lowest weight of abdominal fat pad, carcass and whole body were seen in 100% treatment (P< 0.05) and the highest ratio of carcass to whole weight was seen in 25% treatment which was significantly (P< 0.05) different from other treatments. Chemical analysis of the rapeseed meal showed that the amount of the aliphatic glucosinolates were higher than canola meal. It can be concluded that 25% of soybean meal can be replaced with rapeseed meal in the diet of broiler chicks. For higher levels of replacement, further investigations and better quality meals are required.